2006
DOI: 10.1083/jcb.200602142
|View full text |Cite
|
Sign up to set email alerts
|

DOCK2 is a Rac activator that regulates motility and polarity during neutrophil chemotaxis

Abstract: Neutrophils are highly motile leukocytes, and they play important roles in the innate immune response to invading pathogens. Neutrophil chemotaxis requires Rac activation, yet the Rac activators functioning downstream of chemoattractant receptors remain to be determined. We show that DOCK2, which is a mammalian homologue of Caenorhabditis elegans CED-5 and Drosophila melanogaster Myoblast City, regulates motility and polarity during neutrophil chemotaxis. Although DOCK2-deficient neutrophils moved toward the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
159
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 24 publications
1
159
0
Order By: Relevance
“…Studies in lymphocyte migration also indicated that Dock2 was fully functional to mediate T and B cell chemotaxis in vitro and in vivo in cells lacking PI3K (46). However, Kunisaki et al (22) reported that prolonged inhibition of PI3K with very high concentrations of LY294002 (400 M) did inhibit Dock2 recruitment in mouse neutrophils in response to a fMLP gradient. Moreover, neutrophils isolated from Dock2 knockout mice exhibited inhibition of Rac activation and chemotaxis in response to fMLP stimulation (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in lymphocyte migration also indicated that Dock2 was fully functional to mediate T and B cell chemotaxis in vitro and in vivo in cells lacking PI3K (46). However, Kunisaki et al (22) reported that prolonged inhibition of PI3K with very high concentrations of LY294002 (400 M) did inhibit Dock2 recruitment in mouse neutrophils in response to a fMLP gradient. Moreover, neutrophils isolated from Dock2 knockout mice exhibited inhibition of Rac activation and chemotaxis in response to fMLP stimulation (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kunisaki et al (22) reported that prolonged inhibition of PI3K with very high concentrations of LY294002 (400 M) did inhibit Dock2 recruitment in mouse neutrophils in response to a fMLP gradient. Moreover, neutrophils isolated from Dock2 knockout mice exhibited inhibition of Rac activation and chemotaxis in response to fMLP stimulation (22). In contrast, our Dock2 knockdown HL60 cells showed compromised Rac2 activation, but little inhibition of chemotaxis in response to a CXCL8 gradient in the microfluidic gradient chamber assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Recent studies in mice have uncovered important in vivo roles for DOCK180, DOCK5 and DOCK2 in myoblast fusion, cardiovascular development, osteoclast-mediated bone resorption and immune homeostasis. [7][8][9][10][11] Recent human data has also closely linked deficiencies in DOCK8 to hyper IgE syndromes that can be corrected by transplantation of healthy hematopoietic stem cells in afflicted patients. 12,13 Similarly, studies in cancer cells have highlighted that DOCK3, via its Rac GEF activity, promotes a mesenchymal type of movement 14 while DOCK10, via its Cdc42 GEF activity, supports amoeboid migration.…”
Section: New Modular Domains In Elmo: Defining a Novel Autoregulatorymentioning
confidence: 99%
“…5 This in turn recruits RhoGEFs such as DOCK2 and αPix, which activate Rac and Cdc42 to promote F-actin polymerization and cell polarization. 10,11 In recent years, much work has gone into identifying the mechanisms underlying spatially localized activation of PI3Ks. In Dictyostelium and neutrophils, amplification of the PIP3 signal is mediated by the reciprocal translocation of PI3K to the leading edge and phosphatases, such as phosphatase and tension homology (PTEN), to the lateral and trailing edge of cells.…”
mentioning
confidence: 99%